2017
DOI: 10.5338/kjea.2017.36.3.31
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Kale Seedlings Affected by the Control of Light Quality and Intensity under Smart Greenhouse Conditions with Artificial Lights

Abstract: BACKGROUND:Plant growth under smart greenhouse (that is plant factory system) conditions of an artificial light type is significantly depending on the artificial light sources such as a fluorescent lamps or Light-Emitting Diodes (LEDs) with specific spectral wavelengths regardless of the outside environmental changes. In this experiment, characteristics on the growth and compound synthesis of kale seedlings affected by light qualities and intensities provided by LEDs were mentioned. METHODS AND RESULTS:The kal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…When kale was grown under an artificial light source, the polyphenol content under red light and polyphenol synthesis effect under the mixed light quality of blue + red light was significant. However, the effect of the difference in light intensity was not significant in the two light conditions [ 27 ]. The difference in the polyphenol content of plants under the artificial light source treatment is considered to have a significantly greater effect depending on the color of the light source rather than the light intensity, and it is judged to be due to the difference in the response of plant varieties to the artificial light source.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When kale was grown under an artificial light source, the polyphenol content under red light and polyphenol synthesis effect under the mixed light quality of blue + red light was significant. However, the effect of the difference in light intensity was not significant in the two light conditions [ 27 ]. The difference in the polyphenol content of plants under the artificial light source treatment is considered to have a significantly greater effect depending on the color of the light source rather than the light intensity, and it is judged to be due to the difference in the response of plant varieties to the artificial light source.…”
Section: Resultsmentioning
confidence: 99%
“…The total flavonoid content of root extracts treated with LED red and blue light was found to be higher than that of root extracts treated with other light sources in an experiment using perilla artificial light sources [ 26 ]. In cultivating kale using an artificial light source, it was found that the effect of light intensity on flavonoid synthesis was significant in the blue-white and blue-red mixed-light irradiated groups compared with that in the fluorescent and red light treatment groups [ 27 ]. Unlike polyphenols, flavonoids were found to affect material synthesis via light intensity.…”
Section: Resultsmentioning
confidence: 99%
“…그 중에서도 광질과 광도는 식물의 기내생육 뿐 아니라 순화 에 매우 중요한 요소로서 [7] 순화 후 식물의 생육과 특성을 결 정하는 중요한 환경조건이 된다 [8]. 전통적 순화조건으로서 기 내에서 생육한 식물이 잘 적응하도록 차광을 이용하기도 했지 만 [5] 기술이 발달하면서 외부환경에 영향을 적게 받고, 병해 충 유입이 적으며 다단재배를 통한 재배면적당 수확량이 증가 하는 온실이나 식물공장을 이용하고자 하는 연구가 진행되고 있다 [8]. 식물공장형 육묘배양실에서 식물의 번식과 생산에 이 용하기 위해서는 인공광을 이용한 최적의 생육조건을 찾고자 하는 노력이 선행되어야 한다 [9].…”
unclassified
“…식물공장형 육묘배양실에서 식물의 번식과 생산에 이 용하기 위해서는 인공광을 이용한 최적의 생육조건을 찾고자 하는 노력이 선행되어야 한다 [9]. 발광다이오드(light-emitting diode; LED)가 일반화되면서 온실의 인공광으로 이용하고 있 으며 [9], 광의 파장(광질)을 조절하여 순화 중인 식물의 최적 광조건을 제공함으로써 순화 식물의 생존율과 생육을 개선시 킬 수 있다는 장점이 있다 [8,10]. 국내에서는 식물공장이나 기 내배양에서 인공광을 통한 작물의 재배와 생산을 중심으로 연 구가 진행되고 있어 [11,12] 2).…”
unclassified
“…However effect of the higher NO 3 -N content in the seedling growth was different according to the light qualities considered in the experiment as shown in leaf expansion, pigmentation or dry weight promotion under the single or mixed nutrients. (Ikeda et al, 1992;Tennessen et al, 1994;Morrow, 2008;Inden et al, 2011;Yoon and Choi, 2011;Promratrak, 2017 (Khan et al, 2018a(Khan et al, , 2018bPhibunwatthanawong and Riddech, 2019 (Haddad and Mizyed, 2011;Kozai, 2013;Kumar and Cho, 2014 Hirai et al, 2006;Fan et al, 2013;Shin et al, 2008;Kang et al, 2016 (Fanasca et al, 2006;Caruso et al, 2011;Fu et al, 2017;Khan et al, 2018a (Hirai et al, 2006;Saito et al, 2010;Shimizu et al, 2011 (Cha et al, 2012;Cho et al, 2012;Lee et al, 2012;Kumar and Cho, 2014;Amalfitano et al, 2017;Zhang et al, 2015 (Cardoso et al, 2011;Conti et al, 2014 & Tahboub, 2009;Cardoso et al, 2011;Andersson et al, 2012 (Ikeda et al, 1992;Kang et al, 2013;Heo et al, 2015;Heo et al, 2017…”
mentioning
confidence: 99%